EFFECT OF SLC19A1 GENE POLYMORPHISM AND HAPLOTYPES ON IDIOPATHIC RECURRENT PREGNANCY LOSS AMONG WOMEN IN DUHOK CITY - Darweesh, Hozheen; Eissa, Adil Abozaid (Science Journal of University of Zakho, 2025)
Recurrent pregnancy loss (RPL) affects 1-2% of women of reproductive age and is defined as two or more consecutive losses before 20 weeks of gestation. Idiopathic RPL, which has no known etiology, is increasingly linked to genetic factors, particularly genes involved in folate metabolism. The SLC19A1 gene encodes the reduced folate carrier (RFC1), which is necessary for cellular folate transport. Polymorphisms in this gene may impair folate absorption and homocysteine regulation, potentially leading to poor pregnancy outcomes. This study investigated the relationship between SLC19A1 gene polymorphisms (rs1131596, rs1051266, rs12659) and haplotypes with idiopathic RPL in women from Duhok, Iraq. A case-control study included 70 women with idiopathic RPL and 70 age-matched healthy controls. Genotyping was performed using ARMS-PCR and RFLP-PCR, and statistical analysis was carried out using chi-square, t-tests, and logistic regression. There was no significant association between RPL and the -43T>C or 80G>A polymorphisms. The 696C>T variant showed a marginal association (p = 0.041), with the TT genotype more frequent among RPL cases. Although this suggests a potential link, the result should be interpreted cautiously. Haplotype analysis revealed minimal linkage disequilibrium and no significant associations